2015
DOI: 10.4025/actascianimsci.v37i1.24732
|View full text |Cite
|
Sign up to set email alerts
|

<b>Performance, carcass characteristics and litter moisture in broilers housed at two densities

Abstract: ABSTRACT. The effect of stocking density in broiler chickens (11.08 and 13.20 birds m -2 ), between 5 and 45 days of age, was assessed with regard to performance, cut yield, litter moisture and frequency of pododermatitis injuries. Further, 476 one-day chicks Cobb 500 ® were distributed in a completely randomized design at two densities (birds m -²), with seven replications per treatment in 14 experimental units. Birds housed at a lower density (11.08) increased feed intake (p < 0.05), without any effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…In recent decades, broiler rearing has expanded and higher densities have been used to increase production and decrease fixed costs (Gopinger et al, ). Stocking density is defined as the numbers of birds or weight of birds being reared in a given housing space.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, broiler rearing has expanded and higher densities have been used to increase production and decrease fixed costs (Gopinger et al, ). Stocking density is defined as the numbers of birds or weight of birds being reared in a given housing space.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in flock density reduced the weight gain in 19-38 days of grow-out and the total time of growth, and in the fall feed conversion was high, on average, 3.27. Gopinger et al (2015) increased density from 11.08 to 13.20 m -2 birds and observed that the flock density did not affect broiler performance in the tested range.…”
Section: Semi-intensive and Extensive Way Of Rearingmentioning
confidence: 84%
“…Resultados diferentes podem ser encontrados na literatura, como os de Mendes et al (2012) que verificaram que altas densidades acarretam gravidades nas lesões do coxim plantar de frangos de corte, assim como, Gopinger et al (2015) que observaram que o aumento da densidade de 11,08 para 13,20 aves/m 2 ocasionou maiores ocorrências de lesões, além de favorecer a umidade. Entretanto, Sirriet al (2007) apresentaram resultados semelhantes aos verificados no presente trabalho, em que a densidade de alojamento (11 e 14 aves/m 2 ) não teve influência sobre as lesões de coxim plantar de frangos de corte.…”
Section: Resultsunclassified